Sustainable development of higher education institutions in developing countries: Comparative analysis of Poland and Vietnam - Nguyen Hoang Tien; Nguyen Minh Ngoc; Tran Thi Thuy Trang; Le Doan Minh Duc; Nguyen Phuong Mai (Contemporary Economics, 2022)
This paper discusses sustainable development issues in the higher education sector from the value chain perspective. An adapted value chain is proposed for developing countries that would reflect the specific context of the higher education sector of Poland and Vietnam. Secondary data were collected from two universities in Poland and Vietnam to do a comparative analysis of how sustainability is integrated into the educational value chain. Our analysis shows that the two cases of Poland and Vietnam are quite different in most of the supporting and primary activities when integrating sustainability issues in the educational value chain, except for training. Then recommendations of value co-creation activities in the value chain for higher education institutions in both countries are raised towards achieving sustainable development.
Keywords: M16; 330; business higher education; developing countries; sustainable development; sustainability issues